2017
DOI: 10.1063/1.4974904
|View full text |Cite
|
Sign up to set email alerts
|

An easily fabricated three-dimensional threaded lemniscate-shaped micromixer for a wide range of flow rates

Abstract: Mixing fluid samples or reactants is a paramount function in the fields of micro total analysis system (lTAS) and microchemical processing. However, rapid and efficient fluid mixing is difficult to achieve inside microchannels because of the difficulty of diffusive mass transfer in the laminar regime of the typical microfluidic flows. It has been well recorded that the mixing efficiency can be boosted by migrating from two-dimensional (2D) to three-dimensional (3D) geometries. Although several 3D chaotic mixer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…The simulation and experimental results showed that the micromixer had a high mixing efficiency of 99% for a wide range of low Re (0.003–30). In addition, Rafeie et al [ 148 ] presented an effective micromixer (mixing efficiency > 90%) which incorporates the 3D spiral and fine-threaded microchannels for a wider range of Re (1–1000) ( Figure 20 c).…”
Section: Passive Micromixermentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation and experimental results showed that the micromixer had a high mixing efficiency of 99% for a wide range of low Re (0.003–30). In addition, Rafeie et al [ 148 ] presented an effective micromixer (mixing efficiency > 90%) which incorporates the 3D spiral and fine-threaded microchannels for a wider range of Re (1–1000) ( Figure 20 c).…”
Section: Passive Micromixermentioning
confidence: 99%
“… Schematic of the 3D spiral based micromixer ( a ) with two spiral microchannels and an erect channel; ( b ) with double helical channels in opposite directions; and ( c ) with 3D spiral and fine-threaded microchannel. Reproduced with permission from [ 112 , 113 , 148 ]. …”
Section: Figurementioning
confidence: 99%
“…In other words, trueI¯ HSI ,mix is frame‐dependent. To accommodate frame‐varying mean intensity into the calculation of mixing index, the following equation has been proposed: Mixing index=11Nnormali=1NtrueI¯HSI,itrueI¯HSI,avg2normalIfalse¯HSI,avg0.25em()1normalIfalse¯HSI,avg, where trueI¯ HSI ,avg is the average value of the entire pixels contained in a single image frame.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, I HSI, mix is frame-dependent. To accommodate frame-varying mean intensity into the calculation of mixing index, the following equation has been proposed 6,19,[25][26][27][28] :…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies of spatial formation of materials on the principle of 3D printing have been developed [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. For computer manufacturing in the space of different objects, information on the component composition of the material is needed.…”
mentioning
confidence: 99%